1988
DOI: 10.3109/01485018808986724
|View full text |Cite
|
Sign up to set email alerts
|

Corrected Seminal Fructose Levels: Index of Secretory Activity of Seminal Vesicles

Abstract: Seminal fructose, sperm count, and sperm motility were measured in 340 men attending an infertility clinic. Seminal fructose correlates negatively with sperm count but not with sperm motility. The best correlation between sperm count and seminal fructose was obtained using the logarithm (log) of sperm count. When seminal fructose was multiplied by the log of sperm count obtaining a value named "corrected fructose," the correlation with sperm count disappeared, and there was positive correlation between correct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 15 publications
1
36
0
Order By: Relevance
“…One group of researchers has proposed that absolute fructose concentration is not the best method for measuring seminal vesicle function and has further proposed a ''corrected fructose'' value, which is the fructose concentration (mg/mL) multiplied by the log of the sperm count (mil/mL) (Gonzales et al, 1988(Gonzales et al, , 1993. Gonzales et al showed that this corrected fructose value correlates well with measures of seminal vesicle dysfunction.…”
Section: Fructose and Glucosementioning
confidence: 99%
“…One group of researchers has proposed that absolute fructose concentration is not the best method for measuring seminal vesicle function and has further proposed a ''corrected fructose'' value, which is the fructose concentration (mg/mL) multiplied by the log of the sperm count (mil/mL) (Gonzales et al, 1988(Gonzales et al, , 1993. Gonzales et al showed that this corrected fructose value correlates well with measures of seminal vesicle dysfunction.…”
Section: Fructose and Glucosementioning
confidence: 99%
“…This is further demonstrated by the absence of fructose in the ejaculates of patients with congenital absence of the seminal vesicles [52, 621. Fructose is found in seminal plasma in a range of 1.2-4.0 mg/ml [22], although it is not the only sugar present in the seminal vesicles. Smaller amounts of glucose, ribose, and fucose are also found in these glands.…”
Section: Fructosementioning
confidence: 99%
“…Previously we demonstrated that subjects with levels of serum testosterone below 3 ng/ml have reduced sperm motility and low corrected seminal fructose levels [14]. In the present study, 67% of subjects with hypoprolactinemia showed levels of corrected seminal fructose below normal.…”
Section: Discussionmentioning
confidence: 50%
“…In the present study, 67% of subjects with hypoprolactinemia showed levels of corrected seminal fructose below normal. Corrected seminal fructose is a marker of seminal vesicles function [14], and the function of these glands is mainly under androgenic control [14, 16, 20, 221. Whether, the higher incidence (67%) of subjects with low values of corrected seminal fructose among hypoprolactinemics is associated with the higher incidence (67%) of subjects with low serum testosterone levels in the same group of hypoprolactinemia, or whether hypoprolactinemia has also a direct effect on seminal vesicles function is still unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation